Molecular recognition of N-acetyltryptophan enantiomers by β-cyclodextrin - Chatziefthimiou, Spyros D.; Inclán, Mario; Giastas, Petros; Papakyriakou, Athanasios; Yannakopoulou, Konstantina; Mavridis, Irene M. (Beilstein Journal of Organic Chemistry, 2017)
The enantioselectivity of β-cyclodextrin (β-CD) towards L- and D-N-acetyltryptophan (NAcTrp) has been studied in aqueous solution and the crystalline state. NMR studies in solution show that β-CD forms complexes of very similar but not identical geometry with both L- and D-NAcTrp and exhibits stronger binding with L-NAcTrp. In the crystalline state, only β-CD–L-NAcTrp crystallizes readily from aqueous solutions as a dimeric complex (two hosts enclosing two guest molecules). In contrast, crystals of the complex β-CD–D-NAcTrp were never obtained, although numerous conditions were tried. In aqueous solution, the orientation of the guest in both complexes is different than in the β-CD–L-NAcTrp complex in the crystal. Overall, the study shows that subtle differences observed between the β-CD–L,D-NAcTrp complexes in aqueous solution are magnified at the onset of crystallization, as a consequence of accumulation of many soft host–guest interactions and of the imposed crystallographic order, thus resulting in very dissimilar propensity of each enantiomer to produce crystals with β-CD.
Keywords: β-cyclodextrin; enantiomeric discrimination; N-acetyltryptophan; NMR; X-ray structure